Vertical Phase Separation Structure for High‐Performance Organic Thin‐Film Transistors: Mechanism, Optimization Strategy, and Large‐Area Fabrication toward Flexible and Stretchable Electronics - Yin, Xiaowen; Yang, Junliang; Wang, Haibo (Advanced functional materials, 2022)
Organic thin‐film transistors (OTFTs) exhibit great potential applications in flexible logic circuits, sensors, nonvolatile memory, etc. The vertical phase separation (VPS) structure, deriving from the blends of small molecules and polymers, can produce a high‐quality crystalline semiconducting layer and an intrinsic and trap‐free semiconductor/insulator interface. OTFTs with a VPS structure provide a promising route to accelerate their commercialization due to these desirable features including excellent device performance, good uniformity and reproducibility, environmental and mechanical stability, low‐cost and large‐area fabrication. Additionally, VPS OTFTs also exhibit a good balance between electronical properties and stretchability for intrinsic stretchable OTFTs. Herein, a comprehensive review is given on VPS structure for flexible and stretchable OTFTs. First, the evolution history of VPS structures and its formation mechanism are summarized. Based on the understanding of the VPS structure, the optimization strategies of VPS structures for high‐performance OTFTs are presented. Subsequently, the large‐area fabrication techniques of VPS structures, as well as the potential applications in flexible and stretchable OTFTs, are discussed. Finally, conclusions and outlook are provided for the further development of VPS structure in OTFTs. This review would promote the understanding and development of VPS structures in OTFTs, accelerating its applications in flexible and stretchable electronics. Organic transistors with vertical phase‐separation structures as promising candidates for commercial application exhibit excellent comprehensive performance. This review covers topics ranging from the evolution history of vertical phase‐separation structure, formation mechanisms, and optimization strategy to recent advance and large‐area fabrications, underscoring the understanding of phase separation and their potential applications in flexible and stretchable electronics.